Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Cumulative Review: 20

Answer

$2(x+2)(x^{2}-2x+4)$

Work Step by Step

$2x^{3}+16$ $=2(x^{3}+8)$ $=2(x^{3}+2^{3})$ To simplify the expression further, we will use the equation for the sum of two cubes: $a^{3}+b^{3}=(a+b)(a^{2}-ab+b^{2})$. Therefore, $2(x^{3}+2^{3})=2(x+2)(x^{2}-2x+2^{2})=2(x+2)(x^{2}-2x+4)$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.